ANALISIS EFISIENSI PROSES EMBARKASI DAN DEBARKASI PENUMPANG GUNA KELANCARAN OPERASIONAL KM.KELUD - Hana Safira Apriliana Br.Sitepu; Sahabuddin Sunusi; Senitriany Beatrix Nimot (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the factors causing inefficiency in the passenger embarkation and debarkation process and the efforts to improve its efficiency in order to support the smooth operation of KM. Kelud. This research employed a descriptive qualitative method with data collected through interviews with respondents directly involved in the embarkation and debarkation process, field observations, and documentation studies as supporting data. The results show that the embarkation and debarkation process on KM. Kelud has generally been carried out in accordance with the established Standard Operating Procedures (SOP); however, from the perspective of operational efficiency, several internal and external factors still influence the process. Internal factors include limited service time, limited facilities and infrastructure, passenger baggage handling, and the management of priority passengers, while external factors include the surge in passenger numbers during peak seasons, the presence of non-seat passengers, and congestion in the terminal area. Efforts to improve efficiency can be carried out through adjusting service time during peak seasons, optimizing the use of facilities and infrastructure, controlling passenger flow and baggage, and adding personnel to support the smooth operation of the vessel.